Prokaryotic expression of Cryptosporidium parvum mucin CGD5_2060 and its role in adhesion - YANG Yimin; PAN Lingtao; ZHUANG Haohan; SUN Hongchao; YANG Yi; CHEN Xueqiu; DU Aifang (浙江大学学报. 农业与生命科学版, 2018)
The gene cgd5_2060 was cloned from Cryptosporidium parvum cDNA, and its function-related motifs were predicted. The prokaryotic expression vector pET32a-cgd5_2060 was constructed and transformed into Escherichia coli Rosetta. The recombinant protein CGD5_2060 was expressed and purified, with which the murine polyclonal antibody was prepared, and its antibody titers were determined by indirect enzyme-linked immunosorbent assay (ELISA). The purified recombinant protein CGD5_2060 and control protein were co-cultured with Caco2 cells, and their cell adhesion properties were detected by Western blotting and indirect ELISA. The prediction of CGD5_2060 protein function-related motifs revealed that the 1-19 amino acids of the protein are signal peptides, indicating that the protein is a secreted protein. Using PROSITE database for analysis, the CGD5_2060 protein contains a threonine-rich region, TTTTTTKSTTTTTTAVTT, at 510-527 amino acids; in addition, CGD5_2060 has a cell-attachment related RGD (Arg-Gly-Asp) at 69-71 amino acids. The above results indicated that the cgd5_2060 gene might be associated with C. parvum adhesion to host cells. The recombinant plasmid pET32a-cgd5_2060 was successfully constructed, and a high-quality recombinant protein was successfully purified by nickel column affinity chromatography. The recombinant protein CGD5_2060 had good immunogenicity and polyclonal antibodies with higher titer were successfully prepared. After coincubation of recombinant proteins and Caco2 cells, Western blotting and indirect ELISA revealed that CGD5_2060 could adhere to Caco2 cells. This study provides a theoretical basis for revealing the mechanism of C. parvum adhesion to host cells through preliminary study of cgd5_2060 gene adhesion function.